Hexacyano-[3]-radialene anion-radical salts: a promising family of highly soluble p-dopants. Issue 3 (14th December 2017) - Karpov, Y.; Kiriy, N.; Al-Hussein, M.; Hambsch, M.; Beryozkina, T.; Bakulev, V.; Mannsfeld, S. C. B.; Voit, B.; Kiriy, A.
Abstract : A versatile approach to a family of thermally stable, efficient anion-radical p-dopants having a tunable solubility is developed. Abstract : Organic and inorganic salts of the hexacyano-[3]-radialene anion-radical are readily available and thermally stable compounds (up to ∼180 °C). The tetrabutylammonium salt exhibits an extremely high solubility in a range of solvents (>300 mg l −1 in CHCl3 ) and acts as an efficient p-dopant for poly(3-hexylthiophene) to provide composite films with a conductivity above 2 S cm −1 .